2013
DOI: 10.1111/flan.12033
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Validation of Reading Proficiency Guidelines

Abstract: The validation of ability scales describing multidimensional skills is always challenging, but not impossible. This study applies a multistage, criterion‐referenced approach that uses a framework of aligned texts and reading tasks to explore the validity of the ACTFL and related reading proficiency guidelines. Rasch measurement and statistical analyses of data generated in three separate language studies confirm a significant difference in reading difficulty between the proficiency levels tested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 13 publications
2
18
0
Order By: Relevance
“…Thompson concluded that each skill followed a slightly different and nonparallel development. Like Rifkin (2005), she noted a ceiling effect caused by the exponential nature of the ACTFL scale and suggested that this posed significant problems for developing tests based on the guidelines for reading, writing, and listening (Clifford & Cox, 2013;Cox & Clifford, 2014;Glisan et al, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thompson concluded that each skill followed a slightly different and nonparallel development. Like Rifkin (2005), she noted a ceiling effect caused by the exponential nature of the ACTFL scale and suggested that this posed significant problems for developing tests based on the guidelines for reading, writing, and listening (Clifford & Cox, 2013;Cox & Clifford, 2014;Glisan et al, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…These procedures have been shown to result in high levels of interrater reliability when testing speaking proficiency (Surface & Dierdorff, 2003) and should in fact be used when assessing listening and writing. In addition, recent research has demonstrated that CR testing principles (as depicted in Table 3), including level-by-level test design and floor and ceiling scoring, can be applied to the receptive skills of reading and listening comprehension (Clifford & Cox, 2013;Cox & Clifford, 2014). In addition, recent research has demonstrated that CR testing principles (as depicted in Table 3), including level-by-level test design and floor and ceiling scoring, can be applied to the receptive skills of reading and listening comprehension (Clifford & Cox, 2013;Cox & Clifford, 2014).…”
Section: Nr and Cr Scoringmentioning
confidence: 99%
“…), then there is evidence that the scale can be operationalized as hypothesized. A further discussion of these issues and how they apply to language assessments can be found in Brown, Dewey, and Cox (2014); Clifford and Cox (2013); Cox and Clifford (2014); Eckes (2011);McNamara (1996);and McNamara and Knoch (2012). To apply this model to a proficiencybased EI test, a construct map (Wilson, 2009) was designed to align EI items with the types of speakers who would be successful responding to them.…”
Section: Creating a Proficiency-based Ei Testmentioning
confidence: 99%